Psychological health status of Chinese university students: based on Psychological Resilience Dynamic System Model - Fan, Junqiang; Huang, Yuxin; Yang, Fei; Cheng, Yongjie; Yu, Jingjing (Frontiers in Public Health, 2024)
Based on the Psychological Resilience Dynamic System Model, the mental health status of 3,390 Chinese university students from 15 universities was empirically investigated with the principle of stratified sampling and the geographical distribution and disciplinary diversity of universities,. Among the participants, 47.85% were male and 52.15% were female. Regarding the origin, 42.89% of the students were from rural areas, while 57.11% were from urban areas.. Key findings unveil: (1) A prevalence of 24.54% in students has suboptimal mental health, with 18.70% and 5.84% respectively representing those with poor and relatively poor mental health conditions; (2) A noteworthy negative correlation (P<0.01) between mental health scores of university students and nine pivotal factors, including psychological resilience, self-efficacy, optimism, hope, resilience, family resilience, objective support, subjective support, and support utilization; (3) Eight factors, including grade, family economic status, psychological resilience, self-efficacy, optimism, family resilience, objective support, and support utilization, emerge as significant predictors of university students' mental health (P<0.001), collectively elucidating 57.9% of the total variance in mental health. Based on this, this paper focuses on four recommendations: giving full play to the leading role of universities in mental health education and stress intervention, strengthening the educational power of positive family ideals and role modeling, building a support system for positive social atmosphere and psychological counseling, and improving the self-shaping ability of university students' psychological resilience and positive psychological capital. These recommendations aspire to better promote the mental health of university students and provide a strength reserve for psychological problem intervention.